Early Changes in the Locus Coeruleus in Mild Cognitive Impairment with Lewy Bodies - Železníková, Žaneta; Nováková, L'ubomíra; Vojtíšek, Lubomír; Brabenec, Luboš; Mitterová, Kristína; Morávková, Ivona; Rektorová, Irena (Movement disorders, 2025)
BACKGROUND: Although neuromelanin-sensitive magnetic resonance imaging (NM-MRI) has been used to evaluate early neurodegeneration in Parkinson's disease, studies concentrating on the locus coeruleus (LC) in pre-dementia stages of dementia with Lewy bodies (DLB) are lacking. OBJECTIVES: The aims were to evaluate NM-MRI signal changes in the LC in patients with mild cognitive impairment with Lewy bodies (MCI-LB) compared to healthy controls (HC) and to identify the cognitive correlates of the changes. We also aimed to test the hypothesis of a caudal-rostral α-synuclein pathology spread using NM-MRI of the different LC subparts. METHODS: A total of 38 MCI-LB patients and 59 HCs underwent clinical and cognitive testing and NM-MRI of the LC. We calculated the contrast ratio of NM-MRI signal (LC-CR) in the whole LC as well as in its caudal, middle, and rostral MRI slices, and we compared the LC-CR values between the MCI-LB and HC groups. Linear regression analyses were performed to assess the relationship between the LC-CR and cognitive outcomes. RESULTS: The MCI-LB group exhibited a significant reduction in the right LC-CR compared to HCs (P = 0.021). The right LC-CR decrease was associated with impaired visuospatial memory in the MCI-LB group. Only the caudal part of the LC exhibited significant LC-CR decreases in MCI-LB patients compared to HCs on both sides (P < 0.0001). CONCLUSIONS: This is the first study that focuses on LC-CRs in MCI-LB patients and analyzes the LC subparts, offering new insights into the LC integrity alterations in the initial stages of DLB and their clinical correlates. © 2024 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; alpha-Synuclein; Humans; neuropsychologické testy; lidé středního věku; melaniny; demence s Lewyho tělísky; neuromelanin‐sensitive magnetic resonance imaging; Female; Lewy Body Disease; Aged; senioři; lidé; Neuropsychological Tests; ženské pohlaví; alfa-synuklein; mild cognitive impairment with Lewy bodies; Male; Middle Aged; Melanins; Locus Coeruleus; Cognitive Dysfunction; Aged, 80 and over; senioři nad 80 let; mužské pohlaví; kognitivní dysfunkce; locus coeruleus